Facile synthesis of silver immobilized-poly(methyl methacrylate)/ polyethyleneimine core-shell particle composites - Somkieath Jenjob (2018)
A facile route to synthesize silver-embedded-poly(methyl methacrylate)/polyethyleneimine (PMMA/PEI-Ag) core-shell particle composites was illustrated in this present work. PMMA/PEI core-shell particle templates were first prepared by a surfactant-free emulsion polymerization. PEI on the templates' surface was further used to complex and reduce Ag + ions (from silver nitrate solution) to silver nanoparticles (AgNPs) at ambient temperature, resulting in the PMMA/PEI-Ag particle composites. The formation of AgNPs was affected by the pHs of the reaction medium. The pH of reaction medium at 6.5 was optimal for the formation of PMMA/PEI-Ag with good colloidal stability, which was confirmed by size and size distribution, FTIR spectroscopy, UV-vis spectroscopy and X-ray diffraction. Moreover, the amount of AgNO 3 solution (4.17-12.50 g) was found to affect the formation of AgNPs. Transmission electron microscopy (TEM) indicated that the AgNPs were incorporated in the PMMA/PEI core-shell matrix, and had 6-10 nm in diameter. AgNPs immobilized on PMMA/PEI core-shell particles were also investigated by energy dispersive X-ray spectroscopy analysis mode extended from scanning electron microscopy (SEM/EDS). Furthermore, the presence of AgNPs was found to influence the thermal degradation behavior of PMMA/PEI particle composites as observed through thermogravimetric analysis (TGA). © 2012 Elsevier B.V. All rights reserved.